(untitled) - Mueller, John Paul (Indianapolis, 2006)
This Mastering book from Sybex, offers beginning through advanced instruction, with emphasis on beginner and intermediate topics. Built around practical applications, you'll learn how to create feedback forms, develop a site search, build a shopping cart, use pop-ups and redirection, and much more.
Keywords: Web site development,Microsoft Visual Web Developer (Computer file),Phát triển Website,Microsoft Visual Web Developer (tập tin máy tính)